Energy Consumption Estimation Model as a QoS-Aware Elasticity Support Mechanism for 5G Network Slicing - Martinez, Marvin A. L.; Suruagy, José A.; Machado, Marcia C.; Carvalho, Tereza C.; Martins, Joberto S. B.; Antunes, Sabino R. S.; Donatti, Adnei W.; Correa, Sand; Ferreto, Tiago; Silva, Flávio de Oliveira (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
This paper presents a dynamic energy consumption estimation model for Fifth Generation (5G) Network Slicing (NS) with support for Quality of Service (QoS)-aware elasticity decisions. The model evaluates the admission of a new virtual network function under four controlled scenarios and shows that optimized strategies reduce the additional energy required for admission. The results also identify the EDGE segment as the main point of energy variation. These findings indicate that energy-aware elasticity can improve resource use, reduce energy consumption, and help lower indirect CO2 emissions in sliced networks.